A versatile platform for multilevel modeling of physiological systems - Asai, Yoshiyuki (Henry Stewart Talks, 2014)
Multi-level modeling, Physiome database and mathematical modeling, PhysioDesigner, PHML, simulator & databases, Module and physical-quantity, Mathematical expressions in a model, Reuse of modules, SBML-PHML hybrid modeling, Template and instance framework, Integration of time series data and morphology, Physical-quantity assigned to time-series data, Modeling with morphology, Image processing for integrating morphology, Manipulation on medical images, Integrating morphology with Poisson differential equations (PDEs), Flint simulator, Visualization by PhysioVisualizer and in 3D morphology space, Physiome.jp and PH database, Inter-operation and linkage among applications (Garuda)